Psychological aspects of climate change risk perception: A content analysis in Iranian context - Mehrdad Farrokhi; Hamid Reza Khankeh; Nasir Amanat; Mohammad Kamali; Mohammad Fathi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Risk perception is an important predictor to mitigate climate change effects which can produce mental health consequences such as anxiety and depression. For developing policies of climate risk adaptation, awareness of public attitudes, beliefs, and perception is essential. At this study, researchers tried to focus on the often "unseen" psychological aspects of climate change. MATERIALS AND METHODS: A qualitative approach was done with a consistent content analysis method. The study consisted of 33 participants including ordinary people and experts in disasters and climate change. Purposeful sampling was adopted until data saturation. The data collection was performed through in-depth and semi-structured interviews. All interviews were transcribed after listening again and again and reading several times to catch an overall understanding of the interviews. RESULTS: The main theme of the study was "Complexity nature of climate change risk perception" and related categories including "the Mental health dimension," "the Cognitive dimension" and "Interaction of imposed components." The structure of the research community strongly reflected effects of cultural and religious factors in all aspects of community life. Participants' life experiences of extreme events were associated to their perception of climate change. CONCLUSIONS: Risk perception is multifactorial and complicate and should clearly be understood to improve community participation to manage climate change-related risks. We propose that authorities and related managers should pay attention to it as a priority. This may assist in developing research on public mental health practices.